Development and Testing of Shared Decision Making Interventions for Use in Emergency Care: A Research Agenda. (December 2016) - Melnick, Edward R.; Probst, Marc A.; Schoenfeld, Elizabeth; Collins, Sean P.; Breslin, Maggie; Walsh, Cheryl; Kuppermann, Nathan; Dunn, Pat; Abella, Benjamin S.; Boatright, Dowin; Hess, Erik P.
Abstract: Decision aids are evidenced‐based tools designed to increase patient understanding of medical options and possible outcomes, facilitate conversation between patients and clinicians, and improve patient engagement. Decision aids have been used for shared decision making (SDM) interventions outside of the ED setting for more than a decade. Their use in the ED has only recently begun to be studied. This article provides background on this topic and the conclusions of the 2016 Academic Emergency Medicine consensus conference SDM in practice work group regarding "Shared Decision Making in the Emergency Department: Development of a Policy‐Relevant, Patient‐Centered Research Agenda." The goal was to determine a prioritized research agenda for the development and testing of SDM interventions for use in emergency care that was most important to patients, clinicians, caregivers, and other key stakeholders. Using the nominal group technique, the consensus working group proposed prioritized research questions in six key domains: 1) content (i.e., clinical scenario or decision area), 2) level of evidence available, 3) tool design strategies, 4) risk communication, 5) stakeholders, and 6) outcomes.